2009
DOI: 10.3329/jbsa.v18i1.4036
|View full text |Cite
|
Sign up to set email alerts
|

Use of Oral Bromazepam as Premedicant and it’s Effects in Peri-operative Period - A Comparative Study with Oral Diazepam

Abstract: : . Sedation score that was measured at morning on the day of operation before induction in different groups was seen and found that in (36.66%) patients were drowsy but responds to verbal commands in comparison to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Its pharmacokinetic properties are consistent with rapid complete absorption from the gastrointestinal tract, peak level being attained in between 1-4 hours. The drug is completely absorbed after oral administration and is eliminated from the blood with a mean half-life of 12-20 hours 11 . Lorazepam is the ortho-chlorophenyl derivative of the main metabolite of diazepam, desmethyl-diazepam.…”
Section: Resultmentioning
confidence: 99%
See 1 more Smart Citation
“…Its pharmacokinetic properties are consistent with rapid complete absorption from the gastrointestinal tract, peak level being attained in between 1-4 hours. The drug is completely absorbed after oral administration and is eliminated from the blood with a mean half-life of 12-20 hours 11 . Lorazepam is the ortho-chlorophenyl derivative of the main metabolite of diazepam, desmethyl-diazepam.…”
Section: Resultmentioning
confidence: 99%
“…Sedation score that was measured in the morning on the day of operation, found that in Group D (36.66%) patients were drowsy but responded to verbal commands in comparison to Group B (6.66%) (p<0.001). Postoperatively nausea was more in the diazepam group (20.00%) in the than bromazepam taken group (16.16%)11 . Our study showed moderate anti-anxiety effect of bromazepam and less side effects but did not include diazepam or any control group.…”
mentioning
confidence: 87%
“…Postoperatively nausea was more in diazepam taken group (20.00%) than bromazepam taken group (16.16%). 11 Eman et al performed a prospective double blind randomized trial on 60 healthy infertile female patients who were scheduled for embryo transfer by IVF. They received either Pregabalin (300mg)(group A), Bromazepam (3mg)(group B), or placebo (folic acid 0.5 mg) (group C) 90 min before surgery as oral premedication.…”
Section: Resultsmentioning
confidence: 99%